Time-dependent quantum study of the kinetics of the H(2S)+FO(2?) ? OH(2?)+F(2P) reaction - Gogtas, Fahrettin (Wiley-Blackwell, 2008)
Quantum mechanical wave packet calculations are carried out for the H((2)S) + FO((2)Pi) --> OH ((2)Pi) + F((2)P) reaction on the adiabatic potential energy surface of the ground 3A '' triplet state. The state-to-state and state-to-all reaction probabilities for total angular momentum J = 0 have been calculated. The probabilities for J > 0 have been estimated from the J = 0 results by using J-shifting approximation based on a Capture model. Then, the integral cross sections and initial state-selected rate constants have been calculated. The calculations show that the initial state-selected reaction probabilities are dominated by many sharp peaks. The reaction cross section does not manifest any sharp oscillations and the initial state-selected rate constants are sensitive to the temperature. (C) 2008 Wiley Periodicals. Inc.
Keywords: reaction dynamics; reactive scattering; wave packet study; time-dependent quantum dynamics; HOF reaction